Ethyl acetate synthesis by direct addition of acetic acid to ethylene on a silicotungstic acid catalyst: Experimental assessment of the kinetics - Van Wettere, Bram; Aghakhani, Saleh; Lauwaert, Jeroen; Thybaut, Joris W. (Applied catalysis. A, General, 2022)
The kinetics of the ethyl acetate synthesis by direct addition of acetic acid to ethylene on an industrial silicotungstic acid catalyst have been acquired experimentally by systematically varying the operating conditions. This is essential to assess the effects of the operating conditions on reactant conversions, selectivity towards the main product ethyl acetate and side products, i.e. ethanol and diethyl ether. Conversions benefit from increasing reaction temperature and ethylene concentration and from reducing pressure, acetic acid and water concentrations. Higher acetic acid and lower water concentrations are advantageous for the ethyl acetate selectivity, which is not altered by temperature, pressure and ethylene concentration. Present work is the first publication of experimental kinetics data of this reaction on an industrial catalyst, which is essential to provide qualitative insights in the reaction kinetics, improve understanding and, hence, serve the optimization and innovation of ethyl acetate production plants that apply the direct addition technology.